Edukasi Kepada Pelaku UMKM Tentang Penyusunan Laporan Keuangan Sederhana Di Desa Medan Sinembah - Revita Sari; Rahmat Hidayat; Chairunnisa (AMMA : Jurnal Pengabdian Masyarakat, 2025)
In community service activities in Medan Sinembah Village, Deli Serdang, North Sumatra, the author found that MSME actors still do not understand the importance of a financial report. Business actors and MSME owners only use a book to record without using a method or systematic writing of financial reports. For this reason, the author decided to conduct socialization regarding the introduction of the importance of a financial report by educating on the preparation of simple financial reports because the preparation of financial reports is very important for MSMEs. Through financial reports, business actors can obtain an overview of financial conditions, assist in decision making, and facilitate access to capital. Financial reports allow MSMEs to monitor performance, control costs, and know the position of business profit and loss.